SUMBANGAN HERMENEUTIK KRITIS JURGEN HABERMAS DALAM MENYIKAPI PRAKTIK RADIKALISME AGAMA DI INDONESIA - Alkuinus Babo (Sanjiwani: Jurnal Filsafat, 2025)
The focus of this study is to examine the phenomenon of religious radicalism in Indonesia, which has recently become a trigger for the emergence of destructive, anarchic, and racist attitudes in the communal way of life. The method employed in this study utilizes a qualitative approach dialogued with Jurgen Habermas's critical hermeneutical analysis. Critical hermeneutics, as applied by Habermas, offers a unique perspective in dissecting cases related to socio-political and religious issues grounded in authority and tradition. The findings of this study reveal that Habermas's critical hermeneutics unveils hidden ideological moments behind authority and tradition through reflection and evaluation. This becomes possible through an inclusive attitude in constructing communication with critical and rational awareness. With this awareness, individuals are led to an understanding free from dominant, repressive, and manipulative power. This understanding not only touches the cognitive dimension but also extends to the realm of practice. The contribution of this study lies in presenting a critical and rational approach to address various forms of social disintegration and dehumanizing practices, especially in Indonesia, known as a heterogeneous nation.